Media Pembelajaran Kebutuhan Dasar dan Pemeriksaan Antenatal Care pada Ibu Hamil Berbasis Android pada Masa Pandemic Covid – 19: Learning Media for Basic Needs and Examination Android-Based Antenatal Care for Pregnant Women During the Covid-19 Pandemic - Indra Farah Ni'sa; Syafruddin Syarif; Sri Ramadany (Jurnal Bidan Cerdas, 2022)
Introduction: The spread of the corona virus initially had a huge impact on the economic and social world, now the impact is very clear on the education sector. Physical distancing must be applied, causing the learning process of students in the classroom to change the method by learning from home or learning from home. Midwifery services are a form of health services for pregnant women provided by health workers, namely professional midwives. In improving the quality of health services for pregnant women and their unborn babies. So to realize quality services in midwifery services during this pandemic, educators must create innovations in the form of android-based learning methods so that midwifery students who will become professional midwives remain active in learning, starting from providing an understanding of learning materials and laboratory skills that will support the success of giving service. Objectives: To produce learning media for basic needs and ANC examinations for android-based pregnant women for DIII Midwifery students during the Covid-19 pandemic. Methods: using research and development (R&D) methods, to assess the knowledge level of 34 students using pre-experimental (one group pre test and post test design, purposive sampling technique, data analysis using descriptive statistical analysis and McNemar test). Results: the assessment of learning media in the material expert validation test obtained a value of (95%) with a very decent category. As for the validation of media experts (92.5%) with a very decent category, and to assess the usefulness of the media by using a Technology Acceptance Model (TAM) questionnaire by assessing several aspects including convenience, usability, trust, user intentions, and user behavior are categorized as good. From the results of statistical tests on knowledge before and after being given an intervention in the form of an android-based learning media application, there was a significant difference in knowledge with a p value < where 0.00 <0.05. Conclusion: This application is very suitable to be used as a learning medium for Midwifery students in basic needs material and antenatal care examinations for pregnant women.   ABSTRAK Pendahuluan: Penyebaran virus corona awalnya berdampak pada dunia ekonomi dan sosial, kini dampaknya pada sektor pendidikan, dimana Jaga jarak atau physical distancing harus diterapkan menyebabkan proses pembelajaran peserta didik dalam kelas harus dirubah metodenya dengan learning from home atau belajar dari rumah. Maka untuk mewujudkan pelayanan yang berkualitas dalam pelayanan kebidanan dimasa pandemic ini tenaga pendidik harus menciptakan inovasi berupa metode pembelajaran berbasis android untuk tetap meningkatkan kualitas pembeljaran. Tujuan Penelitian: Menghasilkan media pembelajaran kebutuhan dasar dan pemeriksaan ANC pada ibu hamil berbasis android pada mahasiswa DIII Kebidanan di masa pandemi Covid-19. Metode Penelitian: menggunakan metode penelitian dan pengembangan (Researh and Development (R&D), untuk menilai tingkat pengetahuan 34 mahasiswa menggunakan Preeksperimental (one group pre test and post test design, Teknik yang digunakan purposive sampling, analisa data menggunakan analize descriptive statistic dan uji McNemar. Hasil: penilaian media pembelajaran pada uji validasi ahli materi didapatkan nilai (95%) dengan kategori sangat layak. Sedangkan untuk validasi ahli media (92,5%) dengan kategori sangat layak, dan untuk menilai kegunaan media dengan menggunakan kuisioner. Technology Acceptance Model (TAM) dengan menilai dari beberapa aspek diantaranya kemudahan, kegunaan, kepercayaan, niat pengguna, dan perilaku pengguna dikategorikan baik. Dari hasil uji statistic tentang pengetahuan sebelum dan sesudah diberikan intervesi berupa aplikasi media pembelajaran berbasis android terdapat perbedaan pengetahuan yang signifikan dengan nilai p< α dimana 0,00<0,05. Kesimpulan: Aplikasi ini sangat layak digunakan sebagai media pembelajaran bagi mahasiswa Kebidanan dalam materi kebutuhan dasar dan pemeriksaan antenatal care pada ibu hamil.